Extremism in Pakistan: Time for decisive action - Acharya, Arabinda (2016)
THE STORMING of the Lal Masjid (Red Mosque) in Islamabad was a demonstration of President Musharraf’s resolve against extremism and terrorism. It may signal the start of an all-out war against the growing influence of the Taliban and al Qaeda in Pakistan. Musharraf has vowed that his government will now aim for the complete elimination of extremist elements in Pakistan. As most of those involved in the Lal Mosque stand-off were from the North Western Frontier Province (NWFP), Musharraf’s proposed offensive against the militancy and terrorism can be expected to be focused on these areas. This would also include radical madrassas which have become the incubators for terrorism in Pakistan.